Silk Fibroin: Photocrosslinking of Silk Fibroin Using Riboflavin for Ocular Prostheses (Adv. Mater. 12/2016). Issue 12 (March 2016) - Applegate, Matthew B.; Partlow, Benjamin P.; Coburn, Jeannine; Marelli, Benedetto; Pirie, Christopher; Pineda, Roberto; Kaplan, David L.; Omenetto, Fiorenzo G.
Abstract : Dissolved silk protein mixed with riboflavin can be crosslinked to form an elastic hydrogel in the presence of blue/violet light. Here, a photomask is used by F. G. Omenetto and co‐workers, as described on page 2417, to illuminate the solution, and the unpolymerized silk is rinsed away. These gels have tremendous potential to be used as corneal prostheses.